Biochemical characterisation of Sphingobacterium multivorum (SM) Toll/Interleukin-1 receptor (TIR) domain-containing protein stimulator of Interferon genes (STING) (TIR-STING) domain - Lim, Darryl Jia Hao (Nanyang Technological University, 2023)
The Toll/interleukin-1 receptor Stimulator of interferon genes (TIR-STING) domain plays a pivot role in immune signalling that has been widely conserved throughout evolution history. Activation of this domain would bring about strong immune responses against external pathogens and serves a pivotal role in the immune system. TIR-STING conserved through evolution history uses the CBASS and CGAS sting pathways to protect themselves against pathogens. The innate immune system serves as the first line of defence against invading pathogens, employing a variety of pattern recognition receptors to detect and initiate a rapid response. Then innate immunity employs the usage of Pattern Recognition Receptors (PRRs) to detect and identify molecules released by damaged cells or those commonly found in pathogens. Amongst the PRRs, Toll/Interleukin Receptor (TIR) domains play a significant role in immune signalling and signal transduction when activated providing a strong immune response. The aim of this project is to express the TIR-STING domain of a gram-negative bacterium - Sphingobacterium multivorum (SM) with the intent of optimising the expression and yield of the protein. The species is chosen as it comes from the same family of gram-negative bacteria which has conserved the TIR-STING domain throughout evolutionary history. The protein would then be purified by various purification methods to characterise and identify the potential binding partners. With that we may subject it to Cryo-EM to obtain the biochemical information and atomic structure of TIR-STING.